Towards a Holistic Buddhist Eco-Ethics - Wang, Juan (Religions, 2024)
The debate on Buddhist eco-ethics emerged in the late 20th century and continues to the present day, which fosters the intersection of Buddhist eco-ethics with environmental ethics. However, the current understanding of Buddhist eco-ethics still falls short of a holistic concept. To fill the gap, this paper argues that different macro perspectives should be considered in the process of developing a concept of holistic Buddhist eco-ethics. For this, we firstly attempt to clarify the dispute over the feasibility of Buddhist eco-ethics from the internal, external, and Buddhists’ perspectives. Then, we address the dispute concerning the classification of Buddhist eco-ethics, proposing a typology that accommodates different perspectives. Finally, two methods are suggested to mediate the dispute over Buddhist eco-ethics and justify its holistic concept, that is, regarding Buddhist eco-ethics as a form of virtue ethics and as a product of “engaged Buddhism.” Here, it is also emphasized to include Buddhists’ perspectives when mediating the dispute. Accordingly, we put forward a holistic concept for Buddhist eco-ethics that incorporates three main macro perspectives: ecological ethics in Buddhism, Buddhism in ecological ethics, and Buddhists’ environmental activities. It is hoped that the wisdom of Buddhist eco-ethics can help us forge a path towards a more harmonious and sustainable world in the near future.